Advances in agile and user-centred software engineering : third International Conference on Lean and Agile Software Development, LASD 2019, and 7th Conference on Multimedia, Interaction, Design and Innovation, MIDI 2019, Leipzig, Germany, September 1-4, 2019, Revised Selected Papers /: third International Conference on Lean and Agile Software Development, LASD 2019, and 7th Conference on Multimedia, Interaction, Design and Innovation, MIDI 2019, Leipzig, Germany, September 1-4, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available